Exploring Persephone Fraser’s Trauma in Carley Fortune’s Every Summer After - Natasya, Selvia; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract This study focuses on the causes, effects, and healing process of the psychological trauma that Persephone "Percy" Fraser in Carley Fortune’s Every Summer After endured. This study employs qualitative text analysis to investigate Percy’s emotional journey through a psychological approach grounded in Bessel van der Kolk’s and Shira Assu’s theory. According to this study, Percy’s betrayal of Sam Florek is the root cause of her trauma, which results in feelings of guilt, anxiety, emotional detachment, panic attacks, and compulsive repetition. Returning to Barry’s Bay marks the beginning of her healing, as self-forgiveness, emotional confrontation, and reconnection aid in her recovery, identity restoration, and trust building. The study finds that trauma not only causes emotional pain and behavioral changes but also physical symptoms. Keywords: Trauma, Cause, Effect, Emotional Healing